Epidurals for Free-Flap Grafts: Optimizing Graft Survival and Preventing Complications in the Anticoagulated Patient - Kirk Lalwani; Kate Maureen Ropp (Association of American Medical Colleges, 2013)
Abstract Introduction This narrative problem-based learning module is designed to facilitate group discussion with the integration of clinical knowledge and self-directed learning. It addresses a complex situation involving trauma, neuraxial anesthesia, anticoagulation, free-flap physiology, and compartment syndrome in a setting of multiple treatment teams. Methods After a case presentation, the instructor guides the group through a series of questions, each of which promotes discussion and reviews the available data on the subject. The module provides multiple diagnostic and decision points in which learners must balance the risk versus benefit of available options, and choose a management strategy on the basis of existing and new knowledge of current practice. The module was created based on the authors' personal experience with a similar situation and a subsequent literature search on the issues covered in the module. Selected significant references and current national guidelines were added to the bibliography to enhance the learner experience and highlight current evidence to support the management options presented in the discussion. Results This module was developed for use at the 2004 and 2006 American Society of Anesthesiologists Annual Scientific Meetings and was presented twice to learners (residents, anesthesiology faculty in academic practices, and private practice anesthesiologists) at each meeting. It was also utilized with pediatric anesthesiology fellows at the primary author's institution. In all, the module has been used in a small-group roundtable format six times, with positive feedback from conference attendees and pediatric anesthesiology fellows. Discussion The module can easily be incorporated into a residency, fellowship, or CME curriculum. It has the potential to be implemented as a single 2-hour team exercise, or be divided into two 1-hour sessions depending on time available.